A study on E-Glass fiber reinforced interpenetrating polymer network (vinylester/polyurethane) laminate's flexural analysis. (2020) - Sethu Ramalingam, P.; Mayandi, K.; Srinivasan, T.; Jerin Leno, I.; Ravi, Rajesh; Suresh, G.
Abstract: The usage of fiber reinforced plastic material occupies most of the prominent places in this modern industrial era, which starts from construction industries to automobile sectors. Its versatility and adoptability towards the various applications emphasize their importance as one of the fore most leading and irreplaceable material in most of the predominant areas. In this present work, a series of proportions of vinylester (VER) and (0, 20, 40 wt%) polyurethane (PU) have been blended with each other and concurrently reinforced with E-Glass fiber reinforcement, with the purpose of fabricating the IPN laminate. In order to evaluate the physical strength, their flexural strength of IPN laminate was studied as per ASTM D790 standard. Result reveals that the addition of PU can significantly decreases the flexural stress to strain ratio to the maximum extent, but adversely increases the strain value. To validate this, obtained results from the experimental data's are cross verified with finite element analysis software ANSYS. The load – deflection curves at mid of the laminate were compared with ANSYS data's. The precision of the FEM data's are assessed by comparing with the experimental results, which are shown good agreement. The differences were observed as 8.33%, 0.697%, 1.5944% for 0%, 20%, 40% PU respectively.